Regulatory T cell therapy for multiple sclerosis: Breaching (blood-brain) barriers - Janne Verreycken; Paulien Baeten; Bieke Broux (Taylor & Francis Group, 2022)
Multiple sclerosis (MS) is an autoimmune disorder causing demyelination and neurodegeneration in the central nervous system. MS is characterized by disturbed motor performance and cognitive impairment. Current MS treatments delay disease progression and reduce relapse rates with general immunomodulation, yet curative therapies are still lacking. Regulatory T cells (Tregs) are able to suppress autoreactive immune cells, which drive MS pathology. However, Tregs are functionally impaired in people with MS. Interestingly, Tregs were recently reported to also have regenerative capacity. Therefore, experts agree that Treg cell therapy has the potential to ameliorate the disease. However, to perform their local anti-inflammatory and regenerative functions in the brain, they must first migrate across the blood-brain barrier (BBB). This review summarizes the reported results concerning the migration of Tregs across the BBB and the influence of Tregs on migration of other immune subsets. Finally, their therapeutic potential is discussed in the context of MS.